Maths In The Qur'an: Should The MI Curriculum Adopt An Islamisation Of Science Approach? - Al Ayyubi, Ibnu Imam; Nurhikmah; Prayetno, Eko; Noerzanah, Firda; Rahmawati, Siti (International Journal of Interdisciplinary Research, 2026)
A number of studies have highlighted the importance of integrating Islamic values in science and social learning in madrasahs, but studies that specifically address the Islamisation of mathematics are still very limited. Most of the current MI curriculum adopts a competency-based approach with very little exploration of the relationship between mathematical concepts and Islamic teachings. This study aims to identify Qur'anic verses related to mathematical concepts, analyse the urgency of applying the Islamisation approach in mathematics learning, and formulate strategies for the integration of Islamic values in the MI mathematics curriculum. This research uses a qualitative approach with in-depth interview method. The research was conducted in several MIs that have implemented or attempted to integrate Islamic values in mathematics learning in West Bandung and Makassar. Data were collected through in-depth interviews with teachers, academics and curriculum experts. The interviews were semi-structured to allow the respondents the freedom to express their views in depth. This research highlights the importance of integrating Islamic values in mathematics learning in Madrasah Ibtidaiyah through the Islamisation of science approach. The results showed that although mathematical concepts in the Qur'an have long been recognised, the implementation of the Islamisation approach in the MI curriculum is still limited. Concrete steps are needed to adopt the Islamisation of science approach in mathematics learning in MI. The government and Islamic education institutions need to work together to develop a more integrative curriculum, provide textbooks that reflect the integration of science and Islamic values, and organise training for educators.